A Systematic Review on Semantic-based Ontology for Quranic Knowledge - Salsabila Muhmad Rusli, Asma; Ridzuan, Farida; Mohd Zaki, Zulkifly; Norazizi Sham Mohd Sayuti, M; Abdul Salam, Rosalina (International Journal of Engineering and Technology, 2018)
The Holy Quran ontology models are gaining popularity among researchers due to people’s demands in understanding this divine book. Due to this, there are many studies and research have been conducted in this area to facilitate people’s understanding of the Quran. The Quran knowledge is represented conforming to an ontology within a system framework. This also includes various concepts that are interrelated with the others. From the literature, however, the existing Quranic ontology models do not cover all concepts in the Quran, which limit them to domains such as place nouns, themes, pronouns, antonyms and Islamic knowledge in the Quran. Thus, this research aims to identify relevant research works from various electronic data sources using systematic literature review (SLR) method to provide a comprehensive review of this area. This paper presents a systematic review of the literature related to the existing ontology models, where it leads to disseminating the correct knowledge of the Quran using semantic technologies.